Low-temperature magnetic and thermal properties of the frustrated two-dimensional S = 1 compound Ni5(TeO3)4Cl2 - Khatsko, E.; Nizhankovskii, S.V.; Gnatchenko, S.; Zaleski А.; Lemmens, P.; Berger, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The temperature and magnetic field dependent magnetization of the two-dimensional quantum spin system Ni5(TeO3)4Cl2 has been investigated using single crystals in temperature range 1.8–100 K and in magnetic fields up to 14 T. The magnetization below the magnetic phase transition demonstrates an unusual temperature behavior with considerable anisotropy. Combined magnetization and specific heat data allowed to determine the critical temperature of the magnetic phase transition, Tc = 28.4 K. Magnetic fields shift this temperature toward lower temperatures.